Design and Application for End of Arm Tooling in Plastic Injection Molding - M Lutfi Khanif; Puji Basuki; Niyar Candra A; Hendar Wirawan; Jotho (Nacreva Publisher, 2026)
This study discusses the implementation of End of Arm Tooling (EOAT) in the injection molding production process at Toyoda Kakou Co., Ltd. EOAT is a device attached to the end of a robotic arm that functions to automatically remove products from the mold. The research method used is descriptive qualitative with a case study approach. The evaluation results show that the use of EOAT is able to reduce the cycle time from approximately 26,0 seconds to 22.5 seconds, product defect rate decrease from 4% to 1%, and reduce from 1 employee to zero. This study also presents the detailed cost of EOAT components using the Yushin brand, with a total estimated value of IDR 6,350,000. The conclusion of this research is that EOAT has been proven to improve the efficiency and safety of the production process. It is recommended that EOAT be implemented more widely in other production lines.